ANALISIS KUALITAS LAYANAN, CITRA TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA MASKAPAI PENERBANGAN BATIK AIR RUTE KOTA PEKANBARU-JAKARTA - Muhammad Arif; Sri Restuti; Deny Danar Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted at PT. Lion Mentari Airlines in order to determine how Service Quality, Image either directly or indirectly on Customer Loyalty through of Customer Satisfaction. The sample in this study are 135 cus-tomer at PT. Lion Mentari Airlines, with testing data analysis used in this studyis a Test Validity, Reliability Test, Test Classical Assumptions, Methods Msi. Data analysis methodused is the method of path analysis or path analysis with the help of Statistica Package of Social Science (SPSS) version 21.0. From the proceeds of the test that have been done, the path of Service Quality (X1) significantly impact to Customer Satisfaction (Y1). The result of the path of Image (X2) had a significantly impact to Customer Satisfaction (Y1). The path of Customer Satisfac-tion (Y1) not had significantly impact to Customer Loyalty (Y2). The result of the path of Service Quality (X1) had a significantly impact to Customer Loyalty (Y2). The result of the path of Image (X2) had a significantly impact to Customer Loyal-ty (Y2). The last is, the path of Service Quality (X1) to Customer Loyalty (Y2) through of Customer Satisfaction (Y1) had a direct effect and don’t had indirect effect. The result of the path of Image (X2) to Customer Loyalty (Y2) through of Customer Satisfaction (Y1) had a direct effect and don’t had indirect effect.Keywords: Customer, Satisfaction, Loyalty, Service Quality, and Image.